Barriers to fruit and vegetable consumption among migrant workers in Bangkok: a mixed-methods study - Suvanbenjakule, P.; Schreinemachers, P.; Von Goh, E. (2026)
Background Low fruit and vegetable intake is a major public health concern, especially among marginalized populations. Myanmar migrants in Thailand are vulnerable to poverty and poor diets, but their food environment and behavior have not been studied. The objective of this study was to describe and analyze the fruit and vegetable intake of Myanmar migrant workers in Bangkok. Methods The study combined a quantitative survey of 199 Myanmar migrants working in factories, construction sites, and service industries with in-depth qualitative interviews of 10 migrants. The study analyzed psychological and food environment factors. Results The average fruit and vegetable consumption was 195 g/day, about half the WHO-recommended amount. About a quarter of meals were purchased, and the rest were home-cooked. Quantitative results revealed that home cooking, number of market visits, self-efficacy, and intention are statistically significant predictors of intake. While fresh fruits and vegetables are generally available, key constraints identified in the qualitative analysis included limited mobility, the high cost of fruits and vegetables relative to earned incomes, and long working hours that compel people to prioritize convenience over healthy eating. Conclusions Fruit and vegetable intake is low among migrant workers in Bangkok, putting them at risk of non-communicable disease. There is a need for more targeted strategies to improve migrants’ access to healthy food options.